1985
DOI: 10.1093/oxfordjournals.aje.a114123
|View full text |Cite
|
Sign up to set email alerts
|

Community Exposure to Hazardous Waste Disposal Sites: Assessing Reporting Bias

Abstract: A household health survey of residents living near two hazardous waste disposal sites in Calcasieu Parish, Louisiana was conducted in 1981-1982 as part of a comprehensive study of the effects of those sites on the environment and on the health of nearby residents. An unexposed community was included in the health survey for comparison. Due to media coverage and public concern about the sites, two potential indices of reporting bias, hypochondriasis and respondent's opinion about the environmental effects of wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(40 citation statements)
references
References 7 publications
1
39
0
Order By: Relevance
“…Nine studies (20% ) reported no significant associations between exposures and health effects. There are many possible reasons for insignificance (Roht et al, 1985;Schulman et al, 1993;Acquavella et al, 1994;Nurminen, 1995 ). As examples, the studies suggested the possibility of sampling and measurement bias ( Willis et al, 1993;Garcõ Âa -Rodrõ Âguez et al, 1996;Morris and Knorr, 1996 ), confounding ( Heary et al, 1980;Archer, 1990;Baghurst et al, 1992;Kilburn and Warshaw, 1995;Pope et al, 1995 ) , insufficient sample size and statistical power (Greaves et al, 1981;Matanoski et al, 1981;Brown et al, 1984;Rosenman et al, 1989;Aschengrau et al, 1996 ) , lack of baseline data ( Willis et al, 1993 ) , and residence mobility Pekkanen et al, 1995 ) .…”
Section: Validity Of Residence Location As An Exposure Indicatormentioning
confidence: 99%
“…Nine studies (20% ) reported no significant associations between exposures and health effects. There are many possible reasons for insignificance (Roht et al, 1985;Schulman et al, 1993;Acquavella et al, 1994;Nurminen, 1995 ). As examples, the studies suggested the possibility of sampling and measurement bias ( Willis et al, 1993;Garcõ Âa -Rodrõ Âguez et al, 1996;Morris and Knorr, 1996 ), confounding ( Heary et al, 1980;Archer, 1990;Baghurst et al, 1992;Kilburn and Warshaw, 1995;Pope et al, 1995 ) , insufficient sample size and statistical power (Greaves et al, 1981;Matanoski et al, 1981;Brown et al, 1984;Rosenman et al, 1989;Aschengrau et al, 1996 ) , lack of baseline data ( Willis et al, 1993 ) , and residence mobility Pekkanen et al, 1995 ) .…”
Section: Validity Of Residence Location As An Exposure Indicatormentioning
confidence: 99%
“…Four ofthese studies (1)(2)(3)(4) and several others conducted outside California (6)(7)(8)(9) have documented an increased prevalence of self-reported symptoms associated with exposure to the site. These four California studies and at least two others (6,10) also found an association between concern about the environment and self-reported health problems. This second finding has been suggested in studies of other environmental threats, such as Three Mile Island (TMI) (11), but has only recently begun to receive attention in health surveys of communities residing near waste disposal sites.…”
Section: Introductionmentioning
confidence: 66%
“…This type of assessment is essential to any study that is conducted in a politically charged environment and that relies on a subjective outcome measure, such as symptom reporting. This study was designed to elaborate on the measurement ofthis phenomenon, reporting bias, which has been evaluated in other waste site studies (1)(2)(3)(4)6) and which was the objective ofa Louisiana waste site study (10 In spite ofthe difficulty in determining which particular aspect of perceived risk is most strongly associated with symptom reporting, the findings of this study clearly suggest that symptom reporting is associated with perceived environmental risk. The causal mechanism for this association, ifone exists, is uncertain.…”
Section: Discussionmentioning
confidence: 92%
“…These fears in turn lead to increased symptom reporting, perhaps via activation of the stress response. The strength of a subject's opinions on environmental matters was associated with symptom reporting in those exposed to a hazardous waste site but also in those who were not 82,83 . Those who described themselves as 'very worried' about local environmental conditions were ten times more likely to complain of headaches than those not so concerned 84 .…”
Section: The Civilian Perspectivementioning
confidence: 99%
“…It is unlikely that these complex scientific and political issues will be resolved in the near term. Nor is it likely that research studies conducted after well-publicised disasters will convincingly answer basic scientific questions because of the difficulties of eliminating research biases in highly charged circumstances 82,93,94 . Because health officials cannot provide blanket assurances that such exposures are associated with no, as opposed to low, risk, distrust of medical experts and government officials will continue 95 .…”
Section: The Futurementioning
confidence: 99%